Chapter Extraction and characterization methods for microplastics from estuarine and coastal samplings - Example of the 2019 TARA expedition - Soccalingame, Lata (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
To investigate plastic pollution in rivers, the Tara schooner collected samples from 9 of the main European rivers from May to November 2019. The objectives of the present study are the quantification of the microplastic (MP) contamination and the identification of the chemical nature of microplastics. Thus, extraction methods and automated computer processing for polymer characterization were developed. The three main polymers found were polyethylene (PE), polypropylene (PP) and polystyrene (PS). These results must be compared to the results from other rivers to draw a consistent pattern.